ATTOSECOND INTERFEROMETRY USING A HHG-2ω₀ SCHEME - LORIOT, V.; MARCINIAK, A.; NANDI, S.; KARRAS, G.; HERVÉ, M.; CONSTANT, E.; PLÉSIAT, E.; PALACIOS, A.; MARTIN, F.; LÉPINE, F. (Studia Universitatis Babeș-Bolyai Physica, 2020)
We present an interferometric HHG-2ω0 scheme and compare it to the usual XUV-IR RABBIT method that is widely used in attosecond science. Both methods are able to reconstruct the properties of an attosecond pulse train and can be used to measure attosecond ionization time delays in atoms and molecules. While they have several similarities, they also have conceptual differences. Here, we present some particularities of the HHG-2ω0 method and its advantages and drawbacks, which would help to define situations where it can provide information inaccessible by other technics.